Solid waste raised in the city of Baghdad Environment - Riyadh Daham Tokan; Areaj Khairy Othman (College of Education for Women, 2019)
Most cities in the world are suffering from the problem of solid waste and the resting adverse impact on the environment and public health, in particular the spread of diseases, insects and rodents, As well as the proliferation of nuisance odors result of provided by the responsible parties, As wall as weak environmental awareness among those who dwell in dealing in environmentally sound disposal of solid waste, this study was  bembgesan  first intake of solid waste and the kinds of concept and components by land use, As wall as the effects of solid waste on the environment spatial, factors affecting the quality and quantity of solid waste, the second topic was included as a study field presented the historical city of Baghdad location and population, As wall as private residential role questionnaire, in order to obtain a complete picture of obtain a complete picture of tatertha bmhoreha service and environmental.